2013
DOI: 10.1111/jan.12323
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of the effectiveness of planning strategies in the adherence to medication for coronary artery disease

Abstract: This study has shown that individuals who use action and coping planning report higher adherence to drug treatment, when measured by the global adherence evaluation. Further studies with longer follow-ups are needed to assess if the effect of planning strategies has long-term duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 38 publications
2
39
1
2
Order By: Relevance
“…The null findings for our planning intervention is contrary to the weight of evidence that has tended to support effects of planning interventions on health behaviour, including the relatively few studies that have applied these effects on medication adherence (Brown et al, 2009;Farmer et al, 2012;Jackson et al, 2006;Liu & Park, 2004;Lourenco et al, 2014;O'Carroll et al, 2014;Pakpour et al, 2015). That said, there is research which has found null effects for implementation intentions and other planning interventions (Jackson et al, 2005;Jackson et al, 2006;Jessop, Sparks, Buckland, Harris, & Churchill, 2014;Scholz, Ochsner, & Luszczynska, 2013;Skar, Sniehotta, Molloy, Prestwich, & Araujo-Soares, 2011).…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…The null findings for our planning intervention is contrary to the weight of evidence that has tended to support effects of planning interventions on health behaviour, including the relatively few studies that have applied these effects on medication adherence (Brown et al, 2009;Farmer et al, 2012;Jackson et al, 2006;Liu & Park, 2004;Lourenco et al, 2014;O'Carroll et al, 2014;Pakpour et al, 2015). That said, there is research which has found null effects for implementation intentions and other planning interventions (Jackson et al, 2005;Jackson et al, 2006;Jessop, Sparks, Buckland, Harris, & Churchill, 2014;Scholz, Ochsner, & Luszczynska, 2013;Skar, Sniehotta, Molloy, Prestwich, & Araujo-Soares, 2011).…”
Section: Discussioncontrasting
confidence: 81%
“…Numerous studies have demonstrated that implementation intentions are effective in promoting adherence to medication in epileptic (Brown, Sheeran, & Reuber, ), coronary artery disease (Lourenco et al., ), and hypertensive patients (O'Carroll, Chambers, Dennis, Sudlow, & Johnston, ). In contrast, another study (Jackson et al., ) did not find any effect of implementation intentions in improving adherence to antibiotic medication.…”
Section: Introductionmentioning
confidence: 99%
“…Global Evaluation of Medication Adherence (GEMA): considering the 1. adherence proportion and the 2. observance of the care needed in taking medication, this variable was categorised in: Adherents : appropriate dose and adequate care; or Nonadherents : insufficient dose and/or inadequate care (Jannuzzi, Cintra, et al, ; Lourenço et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Adherents: appropriate dose and adequate care; or Nonadherents: insufficient dose and/or inadequate care (Jannuzzi, Cintra, et al, 2014b;Lourenço et al, 2014).…”
Section: Global Evaluation Of Medication Adherence (Gema)mentioning
confidence: 99%
“…(20) Other studies evaluating the relationship between quality of life and medication adherence in people with chronic diseases have identified influencing factors such as patients' beliefs (self-efficacy), their attitudes and knowledge about the disease treatment (literacy or health literacy), and the health professionals' support for greater empowerment. (21)(22)(23) In this study, factors associated with greater adherence were not investigated, but it is possible that, in line with the literature, the support of health professionals is also an important aspect.…”
Section: Discussionmentioning
confidence: 68%